Cardiac Fibroblast Growth Factor 23 Excess Does Not Induce Left Ventricular Hypertrophy in Healthy Mice - Leifheit-Nestler, Maren; Wagner, Miriam A.; Richter, Beatrice; Piepert, Corinna; Eitner, Fiona; Böckmann, Ineke; Vogt, Isabel; Grund, Andrea; Hille, Susanne S.; Foinquinos, Ariana; Zimmer, Karina; Thum, Thomas; et al. (Frontiers in Cell and Developmental Biology, 2021)
Fibroblast growth factor (FGF) 23 is elevated in chronic kidney disease (CKD) to maintain phosphate homeostasis. FGF23 is associated with left ventricular hypertrophy (LVH) in CKD and induces LVH via klotho-independent FGFR4-mediated activation of calcineurin/NFAT signaling in animal models, displaying systemic alterations possibly contributing to heart injury. Whether elevated FGF23 per se causes LVH in healthy animals is unknown. By generating a mouse model with high intra-cardiac Fgf23 synthesis using an adeno-associated virus (AAV) expressing murine Fgf23 (AAV-Fgf23) under the control of the cardiac troponin T promotor, we investigated how cardiac Fgf23 affects cardiac remodeling and function in C57BL/6 wild-type mice. We report that AAV-Fgf23 mice showed increased cardiac-specific Fgf23 mRNA expression and synthesis of full-length intact Fgf23 (iFgf23) protein. Circulating total and iFgf23 levels were significantly elevated in AAV-Fgf23 mice compared to controls with no difference in bone Fgf23 expression, suggesting a cardiac origin. Serum of AAV-Fgf23 mice stimulated hypertrophic growth of neonatal rat ventricular myocytes (NRVM) and induced pro-hypertrophic NFAT target genes in klotho-free culture conditions in vitro. Further analysis revealed that renal Fgfr1/klotho/extracellular signal-regulated kinases 1/2 signaling was activated in AAV-Fgf23 mice, resulting in downregulation of sodium-phosphate cotransporter NaPi2a and NaPi2c and suppression of Cyp27b1, further supporting the bioactivity of cardiac-derived iFgf23. Of interest, no LVH, LV fibrosis or impaired cardiac function was observed in klotho sufficient AAV-Fgf23 mice. Verified in NRVM, we show that co-stimulation with soluble klotho prevented Fgf23-induced cellular hypertrophy, supporting the hypothesis that high cardiac Fgf23 does not act cardiotoxic in the presence of its physiological cofactor klotho. In conclusion, chronic exposure to elevated cardiac iFgf23 does not induce LVH in healthy mice, suggesting that Fgf23 excess per se does not tackle the heart.